2004
DOI: 10.21000/jasmr04010916
|View full text |Cite
|
Sign up to set email alerts
|

Refinement of Adti-Wp2 Standard Weathering Procedures, and Evaluation of Particle Size and Surface Area Effects Upon Leaching Rates: Part 1: Laboratory Evaluation of Method Performance

Abstract: The second year of method development work was conducted on the ADTI-WP1 (Humidity Cell) and the ADTI-WP2 (Leaching Column) standard test methods. The performance of the leaching column method was superior to the humidity cell method. In making improvements to the leaching column method, variations in column diameter and water-handling/gas-handling procedures were evaluated. Two commercial laboratories and a university research lab participated in the study. Relative percent differences between duplicate sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The status and results of this project are discussed in detail in Hornberger et al, (2004) presented at this meeting Selenium Selenium is a naturally occurring widely distributed element, which shows an affinity for sulfide minerals. It combines with metals and non-metals and may form both organic and inorganic compounds.…”
Section: Kinetic Test Methodsmentioning
confidence: 99%
“…The status and results of this project are discussed in detail in Hornberger et al, (2004) presented at this meeting Selenium Selenium is a naturally occurring widely distributed element, which shows an affinity for sulfide minerals. It combines with metals and non-metals and may form both organic and inorganic compounds.…”
Section: Kinetic Test Methodsmentioning
confidence: 99%
“…Further details are provided in Hornberger et al (2004). The addition of a CO 2 enriched atmosphere is a major departure from many other simulated weathering test methods.…”
Section: Total 100mentioning
confidence: 99%
“…Initial development in phases I and II included evaluation of different test apparatus, effects of particle size, gas composition, leaching frequency and other variables. Phases I and II results are reported by Brady et al (2004) and Hornberger et al (2004). In Phase III, a standard column leaching protocol was used by eight commercial, government and university labs to test five rocks of different lithology, pyrite and carbonate content.…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory-scale column and mesocosm-scale lysimeter experiments have been used to predict TDS release from coal industry materials (overburden, refuse, combustion byproducts) for nearly three decades (e.g., Brady et al, 1998;Clark et al, 2018;Daniels et al, 2014a;Daniels et al, 2016;Daniels et al, 2014b;Hornberger et al, 2004;Orndorff et al, 2015). These studies have shown that (1) rock type and extent of weathering influence TDS release, (2) shales and mudstones release more TDS than sandstones, and (3) unweathered rocks release more TDS than weathered materials.…”
Section: Introductionmentioning
confidence: 99%